Peningkatan Kompetensi Profesional Calon Konselor dalam Menulis Proposal Penelitian - Ardimen Ardimen (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2017)
The purpose of this research is to improve the ability of prospective counselor in writing a research proposal through Problem Based Learning method/ Inquiry (PBL/I) and in particular its purpose is to (1) determine the increased activity of the prospective counselor in writing a research proposal with PBL/I method, and (2) the increase in the ability of prospective counselors in writing a research proposal. This study uses classroom action research with the research subjects were VII semester student majoring BK IAIN Batusangkar. The results of the study in the first cycle showed an increase in activity and the ability of prospective counselors in writing a research proposal. This increase is very varied in accordance with the capability and experience of the students. The results of the second cycle study showed mastery of each indicator, but the indicators are controlled and enhanced by the prospective counselor in the research proposal is; select and formulate the title of the actual and straightforward, choosing and using the concept/ theory/ reference that is current and relevant to support the research problem, enter the empirical facts in the background of the problem, restrict and define problems, formulate objectives in line with the formulation of research problems, formulating usability research, select and use the theory / concept of the actual, choose the appropriate method to the problem and research objectives, and the ability to follow the format of the research proposal.